Adaptation Atlas Notebook: View projected climate impacts / Visualiser les projections d’impacts climatiques - Steward, Peter; Youngberg, Brayden; Joshi, Namita; Ramirez Villegas, Julian; Muller, Lolita; Rosenstock, Todd (2025)
This notebook analyzes projected climate impacts on major crops across Africa, combining yield projections with expected climate-driven changes in temperature and productivity. It allows users to explore how different crops and countries are expected to respond under warming scenarios, quantifying both projected yields and percentage yield losses. The notebook also links each estimate to its underlying study reference and documented adaptation options, helping users compare evidence across crops and regions. This enables a clear understanding of where climate impacts are likely to be most severe and which adaptation practices have been evaluated in the literature.